Certain Sensations Past: A Hysterical Glossary. Issue 2 (November 2014) - Smith, Matthew Wilson
Dubbed 'hysterical' by its alleged editor, this anonymous collection of entries cataloging peculiar sensations of the (principally Western European) nineteenth- century hovers between glossary and glossolalia, raising the question not only of whether it is genuine, but whether it is an article at all.